ANALISIS KUALITATIF FENILALANIN SECARA CHROMATOGRAPHY KERTAS DAN CHROMATOGRAPHY LAPIS TIPIS (Studi Awal Pengembangan Metode Deteksi Penyakit Phenylketonuria) - Begum Fauziyah (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2012)
The qualitative analysis of fenilalanin as paper chromatography and thin layer chromatography is developed as the beginning study of detection phenylketonuria disease. The result of identification qualitatively fenilalanin solution with concentration varia tion using paper chromatography media shows that the clearest spot is gotten by concentration minimal 50 ppm. The result of identification qualitatively fenilalanin solution with variation concentration 1, 3, 5, 10, 25 and 50 (ppm) using thin layer chromatography shows that from the smallest concentration that is 1 ppm, has already give the clear qualitative experiment result, that is purple. Fenilalanin analysis with thin layer chromatography gives more sensitive result than with paper chromatography. memberikan hasil yang lebih sensitif daripada dengan chromatography kertas.